2006
DOI: 10.1002/anie.200600212
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol as a Source for Fuels and Chemicals by Low‐Temperature Catalytic Processing

Abstract: In this era of diminishing petroleum reserves, it is imperative that industrialized society should develop ways to utilize more effectively the abundant and renewable biomass resources available to provide new sources of energy and chemical intermediates.[1] To this end, various processes have been developed to convert biomass and biomass-derived molecules into specialty chemicals (methanol), light alkanes (C 1 -C 6 ), liquid fuels (ethanol and C 7 -C 15 alkanes), and synthesis gas.[2]As a new direction, we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
190
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 307 publications
(202 citation statements)
references
References 27 publications
6
190
0
6
Order By: Relevance
“…In this respect, we have shown that whereas water gas shift is significant during the conversion of glycerol and water at 620 K over a catalyst consisting of Pt supported on ceriazirconia, the rate of water gas shift is negligible at these conditions over Pt supported on carbon. [7] The production of synthesis gas from oxygenated hydrocarbons over a supported metal catalyst such as Pt/C may be limited at low temperatures (e.g., below 570 K) by the desorption of CO from the metal surface. In particular, the heat of CO adsorption on Pt is high (e.g., 130-180 kJ mol À1 , depending on the CO coverage), and unless the CO is converted into CO 2 by the water gas shift reaction, its pressure in the reactor accumulates, leading to high coverages of CO on the Pt surface.…”
Section: Conversion Of Biomass Into Fuels: Aqueous-versus Vaporphase mentioning
confidence: 99%
See 2 more Smart Citations
“…In this respect, we have shown that whereas water gas shift is significant during the conversion of glycerol and water at 620 K over a catalyst consisting of Pt supported on ceriazirconia, the rate of water gas shift is negligible at these conditions over Pt supported on carbon. [7] The production of synthesis gas from oxygenated hydrocarbons over a supported metal catalyst such as Pt/C may be limited at low temperatures (e.g., below 570 K) by the desorption of CO from the metal surface. In particular, the heat of CO adsorption on Pt is high (e.g., 130-180 kJ mol À1 , depending on the CO coverage), and unless the CO is converted into CO 2 by the water gas shift reaction, its pressure in the reactor accumulates, leading to high coverages of CO on the Pt surface.…”
Section: Conversion Of Biomass Into Fuels: Aqueous-versus Vaporphase mentioning
confidence: 99%
“…[62] Indeed, we have found that PtRu and PtRe alloys supported on carbon are excellent catalysts for the conversion of glycerol in water into synthesis gas at temperatures below 570 K, at which temperatures Pt/C catalysts exhibit low catalytic activity. [7] Another pathway outlined in Scheme 6 involves the formation of organic acids by dehydrogenation followed by rearrangement reactions. As noted in Section 3, a hydroxyaldehyde is less stable than a carboxylic acid (e.g., glyceraldehyde is less stable than lactic acid).…”
Section: Conversion Of Biomass Into Fuels: Aqueous-versus Vaporphase mentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary results on the carbonylation of erythritol C 4 H 6 (OH) 4 have shown the formation of pentanoic acid and 2-methylbutyric acid. Furthermore, the reaction of sorbitol C 6 H 8 (OH) 6 with HI has been reported to generate 2-iodo hexane. 39 Nakamura reported the carbonylation of ethylene glycol to give propionic acid and of sorbitol to give heptanoic acid and 2-methyl hexanoic acid.…”
Section: Carbonylation Studiesmentioning
confidence: 99%
“…As a consequence, research into new conversion processes for glycerol as a C 3 platform chemical into value-added products is therefore, both from an economical and from an environmental point of view, of considerable importance. 5 Besides gasification to syngas, 6 several conversions of glycerol are already being explored, for example hydrogenolysis to 1,2-and 1,3-propanediol or the oxidation to dihydroxyacetone. [7][8][9][10][11] Other potential products that are being considered are acrylic acid, glycerol carbonate and epichlorhydrin.…”
Section: Introductionmentioning
confidence: 99%